Developing the VET perspective of students : outcomes of the Pathways2Possibilities Expo in Mississippi - Polk, Deeneaus [Verfasser] (My University, 2016)
"Countries around the world are searching for solutions to their workforce development challenges. Innovation has led to the creation of varying methods of illustrating the world of careers to young people. One such program, Pathways Possibilities (P2P), has begun the process of trying to understand exactly what impact their program has had on their participants. By utilizing survey studies to gain as much feedback as possible, P2P can show what immediate effect their program is having for students, while also highlighting areas of potential moving forward. The article will explore what the data has to offer." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.2 Bildungsverhalten und -verläufe; I 2.3.2 Nordamerika; Beratung; Bildungsverlauf; Berufsverlauf; USA